2017
DOI: 10.1097/ccm.0000000000002013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Muscle Mass by Using Markers of Kidney Function: Development of the Sarcopenia Index

Abstract: The sarcopenia index is a fair measure for muscle mass estimation among ICU patients and can modestly predict hospital and 90-day mortality among patients who do not have acute kidney injury at the time of measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
244
3
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 207 publications
(271 citation statements)
references
References 31 publications
7
244
3
3
Order By: Relevance
“…In order to verify the relationship with muscle mass proven in previous studies [17, 18] and to study its relationship with muscle function (exercise capacity), the correlation between the SI and FFMI and the 6-min walking test was studied in a subgroup of 30 patients. SI correlated with FFMI ( r = 0.431, p = 0.017) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In order to verify the relationship with muscle mass proven in previous studies [17, 18] and to study its relationship with muscle function (exercise capacity), the correlation between the SI and FFMI and the 6-min walking test was studied in a subgroup of 30 patients. SI correlated with FFMI ( r = 0.431, p = 0.017) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The ratio serum creatinine/serum cystatin C (SI) has previously been used as a surrogate marker of muscle mass in amyotrophic lateral sclerosis [23], in patients undergoing physical checkups [24], in ICU patients [17], in lung transplant candidates [18], and in type 2 diabetic patients [25]. All these studies have shown a good correlation of this index with muscle mass, as measured by DEXA, CT scan or electric bioimpedance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations